Mutations affecting a putative MutLα endonuclease motif impact multiple mismatch repair functions - Erdeniz, Naz (2007)
Mutations in DNA mismatch repair (MMR) lead to increased mutation rates and higher recombination between similar, but not identical sequences, as well as resistance to certain DNA methylating agents. Recently, a component of human MMR machinery, MutLα, has been shown to display a latent endonuclease activity. The endonuclease active site appears to include a conserved motif, DQHA(X)(2)E(X)(4)E, within the COOH-terminus of human PMS2. Substitution of the glutamic acid residue (E705) abolished the endonuclease activity and mismatch-dependent excision in vitro. Previously, we showed that the PMS2-E705K mutation and the corresponding mutation in Saccharomyces cerevisiae were both recessive loss of function alleles for mutation avoidance in vivo. Here, we show that mutations impacting this endonuclease motif also significantly affect MMR-dependent suppression of homeologous recombination in yeast and responses to S(n)1-type methylating agents in both yeast and mammalian cells. Thus, our in vivo results suggest that the endonuclease activity of MutLα is important not only in MMR-dependent mutation avoidance but also for recombination and damage response functions.